Gender differences in reactions to injustice. Issue 4 (9th May 2016) - Khoreva, Violetta; Tenhiälä, Aino
Abstract : Purpose: – The purpose of this paper is to examine gender differences in reactions to pay inequity and procedural justice. Specifically, the study seeks to reveal whether these gender differences can be explained by pay comparisons and knowledge of pay. Design/methodology/approach: – Structural equation modeling was utilized to analyze survey data that were combined with archival pay data representing a sample of 416 employees of two universities in Finland. Findings: – Male employees were found to be more sensitive toward pay inequity than female employees. In contrast, procedural justice was more strongly related to the organizational commitment of female than that of male employees. These effects were partly explained by pay comparisons and knowledge of pay. While male employees were more likely to compare their pay with some external referents, female employees were more likely to compare their pay internally. Male employees were somewhat more familiar with the pay system. Differences in these variables relate to organizational commitment. Research limitations/implications: – Given the cross-sectional nature of the study, we encourage future research to look into how gender differences in reactions to injustice evolve over time. Originality/value: – The study provides evidence that female employees react to a lesser extent to pay disparities by continuing to show high commitment toward their organizations. This paradox could be diminished by ensuring that all employees have the same amount of information regarding pay, such as how their pay compares to other referent groups.